2015
DOI: 10.2308/bria-51339
|View full text |Cite
|
Sign up to set email alerts
|

Joint Impact of Materiality Guidance and Justification Requirement on Auditors' Planning Materiality

Abstract: In this study, we examine a setting in which overreliance on structured materiality guidance leads to less appropriate materiality assessments by auditors, and investigate whether a justification requirement in the absence of accountability mitigates this effect. Results from our experiment show that audit managers make less conservative and less appropriate planning materiality assessments in the presence of structured materiality guidance, but that this detrimental effect is mitigated by the need to justify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…An example in this sense could be an accurate review of the materiality thresholds calculated during the audit planning (ISA 320 "materiality in planning and performing an audit") and Chong (2015) expresses the need for a common definition of materiality, especially in a litigious society such as contemporary society. From a different perspective, Audsabumrungrat et al (2016) found that "audit managers make less appropriate materiality planning judgments with structured guidance than with unstructured guidance, and that this detrimental influence of structured materiality guidance is reduced when they are required to justify their materiality judgments". Importantly, their findings are based on a study conducted on Big 4 firms in Thailand, a country that has a market structure and corporate governance mechanisms similar to those in Italy (see Connelly et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An example in this sense could be an accurate review of the materiality thresholds calculated during the audit planning (ISA 320 "materiality in planning and performing an audit") and Chong (2015) expresses the need for a common definition of materiality, especially in a litigious society such as contemporary society. From a different perspective, Audsabumrungrat et al (2016) found that "audit managers make less appropriate materiality planning judgments with structured guidance than with unstructured guidance, and that this detrimental influence of structured materiality guidance is reduced when they are required to justify their materiality judgments". Importantly, their findings are based on a study conducted on Big 4 firms in Thailand, a country that has a market structure and corporate governance mechanisms similar to those in Italy (see Connelly et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Esto es, con el porcentaje de socios firmantes. En este escenario limitado, Audsabumrungrat et al (2016) mediante una metodología experimental 2x2 muestran que, cuando la firma tiene una guía propia para fijar la materialidad, los gerentes de auditoría realizan evaluaciones de materialidad más arriesgadas y menos apropiadas. Entendemos que si la firma tiene una guía propia de materialidad debe ser porque ha alcanzado cierto tamaño, de lo que se puede inferir, aunque con cautela, que tiene un número relevante de socios firmantes y este número está ligado a la fijación de la materialidad.…”
Section: Número De Socios Firmantesunclassified
“…Iskandar e Iselin (1999), Rodriguez (2008), Socol (2008), Audsabumrungrat (2012), Beasley et al (2015) destacam a importância da conceção da materialidade e do risco na condução de uma auditoria e enfatizam a sua relatividade. Aquela permite a exclusão do objeto de análise de um elevado número de transações, o que possibilita que atos ilegais, erros e fraudes não sejam investigados ou filtrados, criando, naturalmente, um expectation gap.…”
Section: Conceitos De Auditoria Não Compreendidos Pelo Público Em Geralunclassified